P–201 The beneficial effects of ZP-free culture on cytoplasmic fragmentation in human embryos. : An innovative trial using 3PN zygotes. (6th August 2021) - Sugishima, M; Yumoto, K; Shimura, T; Mio, Y
Abstract: Study question: Is it possible to culture ZP-free embryos to eliminate perivitelline threads, which are known to be involved in generating cytoplasmic fragments at the first cleavage? Summary answer: ZP-free culturing, an innovative system that decreases the amount of cytoplasmic fragments without disrupting the blastomeres, using incubators with time-lapse imaging. What is known already: A study in 2017 observed perivitelline threads in more than 50% of cleavage-stage human embryos using time-lapse imaging, and the rate of cytoplasmic fragmentation (at the first cleavage) was significantly decreased in embryos without perivitelline threads (P < 0.001). While it has been proposed that perivitelline threads play an important role in crosslinking the cumulus cells and oocyte during maturation, the mechanism underlying such a role remains unclear. It is also unknown whether the threads still function in mature MII oocytes. Study design, size, duration: A prospective study was conducted using 2, 852 normal (2PN/2PB) embryos from c-IVF/ICSI and 113 abnormal (3PN) embryos obtained from c-IVF between 2017 and 2019. The zona pellucida (ZP) of 71 abnormal embryos was removed at the pronuclear stage ("ZP-free"), and the rest (n = 42) were cultured as "ZP-intact". Normal and abnormal embryos were cultured for five days in bench-top incubators (MINC, COOK) and an incubator equipped with a time-lapse imaging system. Participants/materials, setting, methods: Embryos used in this study were donated by 412 couples who underwent c-IVF cycles in our clinic between 2017 and 2019. For ZP removal, 3PN embryos were placed in 0.125M sucrose-containing HEPES media drops to reduce the ooplasm size. Then, ooplasms were completely separated from ZPs by a laser and pipetting. Embryo development and morphology of the three groups (normal, ZP-intact and ZP-free abnormal) were compared based on the degree of cytoplasmic fragmentation. Main results and the role of chance: The first cleavage occurred in 97.8% (n = 2, 790/2, 852) of 2PN/2PB, 83.3% (n = 35/42) of ZP-intact 3PN and 97.2% (n = 69/71) of ZP-free 3PN. Normal (2PN/2PB), ZP-intact and ZP-free 3PN embryos were classified into three groups based on the modified Veeck's criteria thus: <20% fragmented compared to the total volume of cytoplasm at the first cleavage (Grade 1 and 2, Good); 20–39% fragmented (Grade 3, Fair) and ≧40% fragmented (Grade 4, Poor). Of 69 cleaved ZP-free 3PN embryos, 68.1% (n = 47) showed less than 20% fragments which was significantly higher than 2PN/2PB (43.7%, n = 1, 218/2, 790) and ZP-intact 3PN (45.7%, n = 16/35; P < 0.05). Furthermore, 24.6% (n = 17/69) of ZP-free 3PN embryos showed 20–39% fragments which was significantly lower than 2PN/2PB (45.9%, n = 1, 281/2, 790; P < 0.05). In addition, 50.7% of ZP-free 3PN embryos (n = 36) developed to the morula stage after the third cleavage, and 29.6% (n = 21) formed blastocoel and became blastocysts. Thus, removing the ZP before the first cleavage did not adversely affect embryo development and decreased the cytoplasmic fragmentation. Limitations, reasons for caution: Due to ethical and clinical limitations, we only examined abnormally fertilized embryos in this study. Moreover, since the relationship between the perivitelline threads and cytoplasmic fragments is unclear, we plan to conduct molecular biological analysis of the perivitelline threads in further studies. Wider implications of the findings: This study revealed that ZP is not always necessary after the pronuclear stage because ZP-free embryos studied herein developed normally and maintained cell adhesion well. This innovative culture method might provide the breakthrough needed for patients to improve embryo quality who obtain embryos with severe fragmentation caused by perivitelline threads. Trial registration number: Not applicable